582 The impact of glaucomatous disease on lifestyle and healthy aging. Association between structural visual and auditory functional changes in glaucoma (Balneo and PRM Research Journal, 2024)
In the last decade, it was concluded that glaucomatous optic neuropathy is part of the neurodegenerative diseases in which destructive neuronal lesions are located not only in the structure of the retina, but they are also present at the level of the central visual and nervous pathways. The purpose of this study was to evaluate the degree of involvement of the auditory system in patients with Primitive Open Angle Glaucoma (POAG), the structural changes in the optic nerve, and to establish correlation between the hearing loss and structural changes in the optic nerve. Material and methods: It is a prospective, cross-sectional study on 32 eyes of 16 subjects with POAG in a study group and 24 eyes of 12 healthy subjects in control group, with a mean age of 62 years in both groups. Both groups underwent ophthalmological, audiological and brain magnetic resonance imaging (MRI) evaluation. Results: In the Study group patients, compared to the Control group, the average levels of the left Pure-tone audiometry (PTA), the cup/disc (C/D) area in both eyes, and the C/D ratio in both eyes are increased. Conclusions: Patients with POAG show changes in audiometry test in correlation with ophthalmological parameters demonstrating that the auditory system can be affected in glaucoma.